Analisis Konsep Ilmu Islam dan Implikasinya dalam Kependidikan di MI Quraniah 8 Palembang - Kharisma Lujeng Lestari; Sedya Sentosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the concept of Islamic knowledge and its implications in education at MI Quraniah 8 Palembang. The research adopts a qualitative descriptive method with a case study design. Data were collected through interviews, which were then organized, categorized, and interpreted in detail. The findings were presented through a narrative that depicted the research findings. The results of the study indicate that at MI Quraniah 8 Palembang, the concept of Islamic knowledge is significantly integrated into the educational curriculum. Each subject approaches Islamic values closely. The concepts of tauhid (monotheism) and akhlak (morality) are taught through readings, prayers, and internalization in daily life. The role of teachers is crucial in supporting this integration as information providers. Therefore, it can be concluded that the concept of Islamic knowledge is effectively integrated into education at MI Quraniah 8 Palembang. The curriculum and teaching methods are directed towards shaping students' character and faith while integrating Islamic values. It is recommended that MI Quraniah 8 Palembang continues to develop an approach that integrates the concept of Islamic knowledge into the curriculum and teaching methods. Additionally, it is important to involve active participation from parents in supporting education based on Islamic values. In this regard, cooperation between educational institutions, teachers, and parents will strengthen the implementation of holistic Islamic education. Further research can be conducted to deepen the understanding of the effectiveness of integrating the concept of Islamic knowledge in education and its impact on shaping students' character and faith. Keywords: Islam, Education, Concept